The Hidden Structure: The Influence of Residence Hall Design on Academic Outcomes. Issue 3 (27th May 2019) - Brown, Joshua; Volk, Fred; Spratto, Elisabeth M.
Abstract : This study investigates the impact of residence hall architecture on students' academic achievement, also considering the influence of race and homophily opportunity—a tendency to create social bonds with like others. We found that socializing architecture was positively associated with a higher first-semester grade point average, and that homophily opportunity had a significant effect for Black students, but only when those students live in residence halls designed with socializing architecture.